THE JUDICIAL RULINGS PERTAINING TO THE HAGIA SOPHIA IN TURKEY AND THE BABRI MOSQUE IN INDIA: An Analysis - Alam, Mohammad Shekaib; Khaliq, Zaid (UIN Sumatera Utara, 2023)
Abstract: On November 9, 2019, the Supreme Court of India issued a ruling allowing for the construction of a temple dedicated to the Hindu deity Ram on the site of Babri Masjid in Ayodhya, Uttara Pradesh. Similarly, on July 10, 2020, the State of Council, the highest administrative court in Turkey, issued an order to convert the status of Istanbul's Hagia Sophia from a museum back into a mosque. The court's decision in both nations has been regarded as a transformative political development within their respective contexts. This decision has garnered praise from certain individuals, while also attracting criticism from others, both domestically and internationally. This article is thematically based, library-focused, and qualitative. The article examines and evaluates both cases based on the existing evidence pertaining to the historical structures, and endeavours to propose the most persuasive perspective to adopt in such situations. The study's findings suggest that the judicial decision under scrutiny exhibits a greater inclination towards political considerations rather than rational ones.Keywords: Hagia Sophia, Babri Mosque, Judicial Rulings, Recep Tayyip Erdogan, Narendra Modi